EFFECT OF TAX STRUCTURE ON ECONOMIC GROWTH IN NIGERIA: AN EMPIRICAL INVESTIGATION (1999–2023) - AMALACHUKWU CHIJINDU ANANWUDE; FELIX NWAOLISA ECHEKOBA; OGOCHUKWU VICTORIA OBI-NWOSU (Innovare Journal of Social Sciences, 2025)
This study looked at how Nigeria’s tax structure affected the country’s economic growth. Revenue is unquestionably essential for the state to fulfill the social contract by providing for the citizens’ basic needs. This study specifically assessed the effect of the petroleum profit tax (PPT), company income tax, value-added tax (VAT), capital gain tax, and stamp duty on Nigeria’s economic growth. Time series data from 1999 to 2023 were used in the study. The pertinent data were taken from the Federal Inland Revenue Service, Bureau of National Statistics, and Central Bank of Nigeria publications. The Autoregressive Distributed Lag regression analysis approach was utilized. According to the study, PPT and company income tax had a significant effect on Nigeria’s economic growth throughout the study period; however, stamp duty had an insignificant positive effect on economic growth in Nigeria. In the meantime, VAT and capital gains tax significantly hampered Nigeria’s economic growth during the study period. The study suggested, among other things, that the government should start a strategic effort to diversify the economy to boost economic growth and development, especially because petroleum-related sources of income are declining.